Association of N6AMT1 rs2254638 Polymorphism With Clopidogrel Response in Chinese Patients With Coronary Artery Disease - Li, He; Zhang, Yan-Jiao; Li, Mu-Peng; Hu, Xiao-Lei; Song, Pei-Yuan; Peng, Li-Ming; Ma, Qi-Lin; Tang, Jie; Zhang, Wei; Chen, Xiao-Ping (Frontiers in Pharmacology, 2018)
Dual antiplatelet treatment with aspirin and clopidogrel is the standard therapy for patients undergoing percutaneous coronary intervention (PCI). However, a portion of patients suffer from clopidogrel resistance (CR) and consequently with recurrence of cardiovascular events. Genetic factors such as loss-of-function variants of CYP2C19 contribute a lot to CR. Recently, the N-6-adenine-specific DNA methyltransferase 1 (N6AMT1) rs2254638 polymorphism is reported to be associated with clopidogrel response. To validate the association between N6AMT1 rs2254638 polymorphism and clopidogrel response, 435 Chinese CAD patients receiving aspirin and clopidogrel were recruited. N6AMT1 rs2254638 and CYP2C19*2/*3 polymorphisms were genotyped. Platelet reaction index (PRI) was measured by VASP-phosphorylation assay after treated with a 300 mg loading dose (LD) clopidogrel or 75mg daily maintenance dose (MD) clopidogrel for at least 5 days. There was a significant difference in PRI between LD cohort and MD cohort. Carriers of CYP2C19*2 allele showed significantly increased PRI in the entire cohort and in respective of the MD and LD cohorts (p<0.001, p=0.003, p<0.001, respectively). However, carriers of CYP2C19*3 allele exhibited significantly higher PRI only in the LD cohort (p=0.021). PRI value was significantly higher in CYP2C19 PM genotyped patients as compared with those carrying the IM genotypes and EM genotype (p<0.001). Besides, carriers of the rs2254638 C allele showed significantly higher PRI in entire cohort and in the LD cohort (p=0.023, p=0.008, respectively). When the patients were grouped into clopidogrel resistance (CR) and non-clopidogrel resistance (non-CR) groups, CYP2C19*2 was associated with increased risk of CR in the entire cohort, the LD cohort and the MD cohort (p<0.001, p<0.001 and p=0.019, respectively). Carriers of the rs2254638 C allele also showed increased risk of CR in the entire cohort and the LD cohort (p=0.024 and p=0.028, respectively). N6AMT1 rs2254638 remained as a strong predictor for CR (TC vs TT: OR=1.880, 95% CI=1.099-3.216, p=0.021; CC vs TT: OR=1.930, 95% CI=1.056-3.527, p=0.032; TC + CC vs TT: OR=1.846, 95%CI=1.126-3.026, p=0.015) after adjustment for confounding factors. Our study confirmed the influence of CYP2C19*2 and rs2254638 polymorphisms on clopidogrel resistance in Chinese CAD patients. Both CYP2C19*2 and N6AMT1 rs2254638 polymorphism may serve as independent biomarkers to predict CR.